A qualitative exploration of community stakeholders perspectives on dengue outbreak management in urban Nepal: navigational insights and challenges - Sushmita Ghimire; Devendra Raj Singh (Tropical Medicine and Health)
Abstract Introduction Dengue outbreaks are a recurring public health challenge in urban areas of Nepal, necessitating proactive engagement of community stakeholders to ensure effective prevention and control measures. However, there is limited evidence of community engagement in dengue management in urban settings in Nepal. This study aimed to assess the community stakeholders’ perceptions and experiences on dengue outbreak management in urban settings in Nepal. Method A qualitative study with interpretive phenomenology approach was conducted among community leaders and female community health volunteers (FCHVs) who were directly involved in the prevention and control of Dengue outbreaks in Lalitpur Metropolitan City. The participants were selected based on the purposive sampling with inclusion criteria. Twenty face-to-face, in-depth interviews were conducted between April 2023 and June 2023 among the local community stakeholders. The data were analysed using a thematic analysis approach guided by the Health Belief Model as a theoretical framework. Results Findings are presented under two broader themes (i) Community contributions in awareness building, and (ii) Stakeholders’ experiences on dengue management and prevention. The study identified perceived severity and susceptibility, driven by recurrent dengue outbreaks, as key motivators for stakeholders engagement and actions in dengue outbreak management. Community-based initiatives, such as awareness programs and home-to-home visits, were considered effective in increasing public engagement. However, challenges such as delayed actions, the community’s limited knowledge of dengue prevention and control, reluctance for consistent source reduction, inadequate water supply, and adverse sociocultural practices posed significant barriers to dengue management. Despite these obstacles, stakeholders expressed strong self-efficacy and commitment to the prevention and control of potential dengue outbreaks in future. Conclusion Local stakeholder engagement was considered crucial in dengue outbreak prevention and control. However, proactive, timely planning, continuous dissemination of dengue education, improved health infrastructures, and enhanced collaboration and coordination among community members and authorities are essential for the effective management of dengue outbreaks.